2014
DOI: 10.1158/1541-7786.mcr-14-0080
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Apoptosis Is Impeded by Direct Binding of the APL Fusion Protein NPM-RAR to TRADD

Abstract: A subset of acute promyelocytic leukemia (APL) cases have been characterized by the t(5;17)(q35;q21) translocation variant which fuses nucleophosmin (NPM) to retinoic acid receptor alpha (RARA). The resultant NPM-RAR fusion protein blocks myeloid differentiation, and leads to a leukemic phenotype similar to that caused by the t(15;17)(q22;q21) PML-RAR fusion. The contribution of the N-terminal 117 amino acids of NPM contained within NPM-RAR has not been well studied. As a molecular chaperone, NPM interacts wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…We have previously shown that NPM-RAR interacts with TRADD, and inhibits TNF-R mediated activation of the extrinsic apoptosis pathway[16]. We now show that NPM-RAR does not impede TNF-mediated activation of either NFκB or JNK pathways.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…We have previously shown that NPM-RAR interacts with TRADD, and inhibits TNF-R mediated activation of the extrinsic apoptosis pathway[16]. We now show that NPM-RAR does not impede TNF-mediated activation of either NFκB or JNK pathways.…”
Section: Discussionmentioning
confidence: 50%
“…Nuclear TRADD has been implicated in regulating an ill-defined caspase 9-dependent, capase 8-independent apoptotic pathway. Our prior immunofluorescent localization studies indicated that NPM-RAR was expressed primarily in the nucleus, but to a lesser extent in the cytoplasm as well[16]. We speculated that the cytoplasmic component was responsible for the interaction with TRADD, but it is possible that the nuclear component could also interact with nuclear TRADD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, unlike ZBTB16-RARα, NPM-RARα interacts with coactivator and corepressor proteins in a manner similar to that involving PML-RARα [53]. NPM-RARα also binds to the tumor necrosis factor receptor type-I-associated death domain protein and selectively inhibits caspase activation, while allowing NF-κB and JNK activation that stimulates cell growth and promotes survival [54,55], which might be a novel mechanism underlying the role of NPM-RARα in the etiology of leukemia.…”
Section: Introductionmentioning
confidence: 99%